(untitled) (Revista Direito em Debate, 2022)
The social model of deficiency is a paradigm of thinking and acting that considers itself as a social, cultural and relational theme, asserting that exclusion is not centered on the individual, but on the environment inadequate for diversity. Law as a science and experience plays an important role in the introjection of the social model in people’s lives and in the state practice, notably through legislative activity. In this sense, the aim of this paper is to know how the normativity of the legislation of Maranhão (a state in the northeast region of Brazil) manifests with regard to the recognition (or not) of the social model of deficiency. Using an exploratory and descriptive method, the state laws on deficiency until 2018 was listed, highlighting their main contributions and their technical and ideological vicissitudes. It is provisionally concluded that the legislation of that federative unit of Brazil is slowly moving towards the insertion of the social model, however, with remnants of the analysis model of deficiency with a pathological medical filter.